TEACHING STRATEGIES TO OVERCOME THE LOW ACADEMICAL PERFORMANCE OF STUDENTS IN THE FIRST COURSES - Cañete Britez, Walter; Darío Torales Ojeda, Amado (Revista Gênero e Interdisciplinaridade, 2022)
This work addresses the issue of strategies that can be implemented to overcome the low performance of students at the Faculty of Administrative Sciences and Accounting of the UPE. This study focuses on the different factors that affect the academic performance of the student in the first courses. On the other hand, the importance as an institution of carrying out the follow-up and applying the different strategies necessary in this process was verified, for which the teachers and students of the first courses of this Faculty were surveyed. The work develops in the conceptual framework the theoretical bases of the research focusing on the different factors associated with academic performance, the motivational, psychosocial and institutional factors. The methodology used in the investigation was a combined quantitative and qualitative method. The subjects of the sample were 100 students and 15 teachers of the first courses of the three careers of this Faculty, For the analysis of the results obtained, a descriptive statistics and a quantitative analysis of the responses of the subjects of the sample were adopted. The main hallazgos of the investigation, both in the results of the surveys of the students and in the revision of the documents, are that, in fact, there is a percentage of students who have difficulties in carrying out the transition from secondary school to university level because of what is important the implementation of strategies to be able to meet the needs of these students, Based on these observations, it is suggested some strategies that can be applied as an institution to meet these students’ needs and in this way raise the academic performance of the first students courses.